Compensating for source depth change and observing surface waves using underwater communication signals - Ijaz, S. (2012)
Underwater communications impose great challenges due to the unpredictable changes in the environment. In order to accommodate for these changes, equalizers are used to track the Impulse Responses (IRs) and compensate the intersymbol interference (ISI). Source and array depth shifts are one of the major contributing factors to continuous amplitude and phase changes in IR. These changes magnify the problem of data processing in which correlation between successive received signals is involved, e.g. passive Time Reversal (pTR) where a probe signal is sent ahead of the data for post cross-correlation. In this paper, an environment based algorithm is used for pTR equalization, where an appropriate frequency shift of the estimated IR compensates for the geometric changes such as source and array depth shifts. We have applied this Frequency Shift pTR equalizer (FSpTR) on real data collected from Underwater Acoustic Barrier 2007 (UAB’07) sea trial having 1000 baud BPSK signaling at carrier frequency of 6.25 KHz with a sudden source depth change of 0.5 m at various known instants of time. The results illustrate that a considerable gain can be attained using the environment based equalizer in the presence of source and/or array depth changes. Moreover by close analysis of the FSpTR results we have detected surface wave motion through the frequency shifts caused by the array depth variations.